(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
This article presents a methodology for digital diagnostics and monitoring of subjects’ activity in inclusive education within the teaching of Information Technologies. The scientific-practical role of the concepts of data, indicator, metric, and analytics in an inclusive environment is substantiated; the subject–subject system effectiveness digital analysis model, SMART-based diagnostic framework, and information-didactic support implementation technologies are detailed. Experimental results confirm the effectiveness of the methodology.